Study on Immunomodulatory Activity of Dietary Garlic in Chickens Vaccinated against Avian Influenza Virus (Subtype H9N2) - Jafari, R.A.; Ghorbanpoor, M.; Diarjan, S. Hoshmand (International Journal of Poultry Science, 2009)
Fresh garlic powder was evaluated for ability to potentiate the immune response of broiler chicks to Avian Influenza Virus (AIV) vaccine. For this purpose, 280 day-old chicks (Ross 308) were randomly allocated to 4 groups A, B (52 each) C and D (88 each). The birds in groups A and B were given control diet during the experiment, but those in groups C and D received diet supplemented with 1 and 3% garlic powder, respectively. After 2nd bleeding, half of the chicks in groups C and D were separated as groups E and F and fed control diet thereafter. On 9th day of age, the chicks in all groups except A were immunized subcutaneously against AIV (subtype H9N2) with a commercial oil-based inactivated vaccine (Merial, France). Fifteen chicks from each group were bled on days 14, 24 and 34 post vaccination and also 5 just before vaccination. The sera were used for antibody titration against AIV by both HI and ELISA tests. The results showed that antibody levels were considerably higher in the vaccinated chicks than those in the non-vaccinated control throughout the experimental period (p0.05). In addition, the removal of garlic from diet had no significant (p>0.05) effect on serum titer. It is suggested that diet supplementation with garlic powder can not stimulate the humoral response of chickens against AIV vaccine.